Low‐intensity land‐use enhances soil microbial activity, biomass and fungal‐to‐bacterial ratio in current and future climates. Issue 11 (6th September 2021) - Sünnemann, Marie; Alt, Christina; Kostin, Julia E.; Lochner, Alfred; Reitz, Thomas; Siebert, Julia; Schädler, Martin; Eisenhauer, Nico
Abstract: Progressing climate change and intensified land‐use exert unprecedented pressures on soil microbial communities, thus endangering the essential ecosystem functions they provide. However, these global change factors do not act in isolation from each other, making ecosystem consequences hard to predict. To address this knowledge gap, we tested the interactive effects of climate change and land‐use intensity on soil microbial activity, biomass and community composition in a large‐scale field experiment. We tested soil microbial responses to a future climate scenario (ambient climate vs. increased temperature by +0.6°C and altered rainfall patterns) in two land‐use types (cropland vs. grassland) with two levels of land‐use intensity each (high‐intensity vs. low‐intensity). While high‐intensity land‐use is characterized by fertilization and pesticide use, low‐intensity land‐use refrains from both. We measured soil microbial activity and biomass twice per year within a 5‐year period and used phospholipid fatty acid analysis to explore changes in microbial community composition. In contrast to our expectations, soil microbes remained largely unaffected by future climate conditions. However, we found evidence that not just the type of land‐use, but also their respective management intensity (high vs. low) had strong effects on soil microbes. Low‐intensity management promoted soil microbial activity and biomass in grasslands, but this beneficial effect needed several years to establish. Moreover, we show that low‐intensity management increased AM fungi and fungal‐to‐bacterial ratios in croplands as well as grasslands. Our study shows that farmers can promote soil ecosystem functions through low‐intensity management measures. In grasslands, low‐intensity management measures such as high plant diversity consisting of grasses, forbs and legumes, and no mineral fertilization improve soil microbial activity and biomass, as well as the fungal‐to‐bacterial ratio. On arable land, compliance with EU organic farming regulations improves the fungal‐to‐bacterial ratio. We conclude that low‐intensity management can have positive effects on efficient carbon storage, nutrient cycling, soil erosion control and ecosystem multifunctionality under different land‐use and climate change scenarios. Abstract : Our study shows that farmers can promote soil ecosystem functions through low‐intensity management measures. In grasslands, low‐intensity management measures such as high plant diversity consisting of grasses, forbs and legumes and no mineral fertilization improve soil microbial activity and biomass, as well as the fungal‐to‐bacterial ratio. On arable land, compliance with EU organic farming regulations improves the fungal‐to‐bacterial ratio. We conclude that low‐intensity management can have positive effects on efficient carbon storage, nutrient cycling, soil erosion control and ecosystem multifunctionality under different land‐use and climate change scenarios. Zusammenfassung: Der fortschreitende Klimawandel und eine immer intensivere Landnutzung üben einen noch nie dagewesenen Druck auf die mikrobielle Gemeinschaft des Bodens aus und gefährden damit wichtige Ökosystemfunktionen. Faktoren des globalen Wandels wirken jedoch nicht unabhängig voneinander, sondern immer gemeinsam, sodass die Folgen für Ökosysteme schwer vorherzusagen sind. Um diese Wissenslücke zu schließen, haben wir in einem groß angelegten Feldexperiment die interaktiven Auswirkungen des Klimawandels und der Landnutzungsintensität auf die Aktivität, Biomasse und Zusammensetzung der mikrobiellen Gemeinschaft im Boden untersucht. Wir testeten die Reaktionen der Bodenmikroben auf ein zukünftiges Klimaszenario (Umgebungsklima vs. Temperaturanstieg um +0, 6°C und veränderte Niederschlagsmuster) in zwei Landnutzungstypen (Ackerland vs. Grünland) mit jeweils zwei Intensitätsstufen der Landnutzung (hohe Intensität vs. geringe Intensität). Während die intensive Landnutzung durch Düngung und Pestizideinsatz gekennzeichnet ist, verzichtet die Landnutzung geringerer Intensität darauf. Wir haben die mikrobielle Aktivität und Biomasse des Bodens über einen Zeitraum von fünf Jahren zweimal pro Jahr gemessen und Veränderungen in der Zusammensetzung der mikrobiellen Gemeinschaft mit Hilfe der Phospholipidfettsäureanalyse untersucht. Im Gegensatz zu unseren Erwartungen blieben die Bodenmikroben von den künftigen Klimabedingungen weitgehend unbeeinflusst. Wir fanden jedoch Hinweise darauf, dass nicht nur die Art der Landnutzung, sondern auch die jeweilige Bewirtschaftungsintensität (hoch oder niedrig) starke Auswirkungen auf die Bodenmikroben hatte. Eine Bewirtschaftung mit geringer Intensität förderte die Aktivität der Bodenmikroben und die Biomasse im Grünland, aber es dauerte mehrere Jahre, bis sich dieser positive Effekt einstellte. Darüber hinaus zeigen wir, dass eine Bewirtschaftung mit geringer Intensität das Vorkommen von arbuskulären Mykorrhizapilzen und das Verhältnis von Pilzen zu Bakterien sowohl im Ackerland als auch im Grünland erhöhte. Unsere Studie zeigt, dass Landwirte die Ökosystemfunktionen des Bodens durch Bewirtschaftungsmaßnahmen mit geringer Intensität fördern können. Im Grünland verbessern Bewirtschaftungsmaßnahmen mit geringer Intensität wie eine hohe Pflanzendiversität aus Gräsern, Kräutern und Leguminosen und der Verzicht auf Mineraldüngung die mikrobielle Aktivität und Biomasse im Boden sowie das Verhältnis von Pilzen zu Bakterien. Auf Ackerland verbessert die Einhaltung der EU‐Verordnung für den ökologischen Landbau das Verhältnis von Pilzen zu Bakterien. Wir kommen daher zu dem Schluss, dass eine Bewirtschaftung mit geringer Intensität positive Auswirkungen auf eine effiziente Kohlenstoffspeicherung, den Nährstoffkreislauf, den Schutz vor Bodenerosion und die Multifunktionalität von Ökosystemen unter verschiedenen Landnutzungs‐ und Klimawandelszenarien haben kann.